Sustainable development modules: algorithm development and implementation in university educational programs - Bespalyy, Sergey; Mussina, Alma; Kolesnikov, Yuriy; Bespalaya, Yelena; Prokhorov, Egor (Frontiers in Education, 2025)
This study analyses the experience of integrating sustainable development modules into the curricula of two Kazakh universities. Unlike most Western models, the project is adapted to the conditions of a developing country, taking into account limited resources and institutional barriers. Key findings include an increase in students’ knowledge, but a group of “ecological indifference” was identified that requires special pedagogical approaches. Practical difficulties, such as resistance from teachers, and the rigidity of the curriculum reduce the effectiveness of integration. The study offers not only an implementation algorithm, but also a framework for its adaptation in other post-Soviet contexts, filling a gap in the literature on sustainable development for developing regions.